Quo Vadis Potensi Kelautan Indonesia - Gunawan Widi Santosa (Unisia, 2005)
Indonesia has an enourmous potency in marine and fishery resources. However, this potency of living and non-living resources has not been optimally utilized. National development based on marine and fishery sector is a stretegic step forward for national sustainable and justice development. For this purpose it is needed an internal strengten to all sectors such as institution, policy, human resources, and data information so that during exploitation will not face problemss in environmental as well assustainability of the resources.